A dialectic of dreams and dispossession: the school-to-sweatshop pipeline. (January 2016) - Cahill, Caitlin; Alvarez Gutiérrez, Leticia; Quijada Cerecer, David Alberto
Engaging the contradictions of global restructuring that produce the school-to-sweatshop pipeline for undocumented students, our analysis makes visible the relationship between racialized cultural practices of exclusion in educational spaces and the production of 'illegality'. Our theorizing draws upon participatory action research with intergenerational community partnerships based in Salt Lake City, Utah, that share commitments to the collective participation and action of those most affected by the 'intimate dispossessions' of capital accumulation. In our inquiry, we attend to the places and practices of social reproduction – the school, family and home – mining the loopholes of policy and the contours of subjectivity to uncover the critical potential of everyday struggles.